Sertoli cells-only syndrome: current clinical approaches and ongoing research trends - Eugeni, Elena; Arato, Iva; Mancuso, Francesca; Brancorsini, Stefano; Luca, Giovanni; Kofler, Sieglinde (Frontiers in Endocrinology, 2025)
Sertoli Cells-Only Syndrome (SCOS), also known as Del Castillo syndrome or germ cell aplasia, is the most frequent cause of non-obstructive azoospermia, being found in 26-57% of patients affected by this condition. Although up to 10% of infertile males seeking medical attention are affected by SCOS and almost 80 years have already passed since this challenging syndrome was first described, therapeutic approaches to date are modest. The etiology of SCOS involves a large number of causes, including Y-chromosome microdeletions, trauma, viral infections, exposure to radiation or toxins, or idiopathic causes. The seminiferous tubule may be involved in its entirety or affected in a focal pattern only, with residual islands of spermatogenesis, which explains the variability in the success rate of sperm recovery in these patients. No prognostic markers, hormonal or of other nature, are currently employed in clinical practice. The purpose of this review is to organize the known information on SCOS and define current correct diagnostic and clinical practice, focusing in the second section on areas of research to look out for in terms of potential practical developments from the vast knowledge accumulated over recent decades.